Strategi Dakwah Laskar PCR Dalam Pelaksanaan Dakwah di Desa Sembadak Kecamatan Pemulutan Kabupaten Ogan Ilir - Dini, Sapta; Puspita Dewi, Emi (Social Science and Contemporary Issues Journal, 2024)
This skirpsi entitled "Laskar PCR Da'wah strategy (lovers of the Prophet) in the implementation of Da'wah in Sembadak Village, Pemulutan District, Ogan Ilir regency". This research is motivated by the lack of interest in the village community towards the implementation of Da'wah. The purpose of this study is to determine how the Laskar PCR da'wah strategy in the implementation of Da'wah in Sembadak Village and the supporting and inhibiting factors of the Laskar PCR da'wah strategy in the implementation of Da'wah in Sembadak Village. This type of research is qualitative research, with secondary and primary data sources. Data collection techniques using observation techniques, interviews, and documentation. Data analysis techniques in this study are descriptive qualitative by means of data reduction, data presentation, and conclusion. The theory used by Samsudin and Febrini. Based on the results of this research, the DA'wah strategy carried out by Laskar PCR (lovers of the Prophet) has succeeded in increasing the interest of the Sembadak Village community in Da'wah activities through a personal approach strategy, and social media. Through these efforts, it helps people understand religious matters and invites them to be active in Da'wah activities. Factors supporting Laskar PCR's da'wah strategy include material support and resources as well as cooperation with community leaders. While the inhibiting factor of Laskar PCR's da'wah strategy is the lack of public interest in Da'wah activities caused by a lack of understanding of the importance of Da'wah, different priorities in everyday life, and low levels of Education.